Theorizing the Dark Side of Inter-organizational Relationships: An Extension - Pillai, Kishore Gopalakrishna; Sharma, Piyush; Cornelissen, Joep; Zhang, Yumeng (Emerald, 2023)
Abstract Purpose This paper aims to propose mechanisms of the dark side of interorganizational relationships from a social psychological perspective. The purpose is to understand the role of boundary spanners’ social psychological processes that may trigger the dark side effects.